Independensi Otoritas Jasa Keuangan (Pasca Diundangkan Undang-Undang Nomor 4 Tahun 2023 tentang Penguatan dan Pengembangan Jasa Keuangan) - Upita Anggunsuri; Zahara (Fakultas Hukum Universitas Islam Indonesia, 2024)
This research aims to analyze the independence of the Financial Services Authority (OJK) after the promulgation of Law No. 4 of 2023 on the Development and Strengthening of the Financial Services Sector. This research addresses the following problems, how independent is the OJK after the promulgation of Law No. 4 of 2023 on the Development and Strengthening of the Financial Services Sector; and what are the challenges faced by OJK in building relationships between financial services sector developments after the promulgation of Law No. 4 of 2023 on the Development and Strengthening of the Financial Services Sector. This research uses a normative juridical method with statutory and conceptual approaches. This research concludes that the enactment of Law No. 4 of 2023 on the Development and Strengthening of the Financial Services Sector poses challenges in maintaining the independence of the OJK in carrying out its authority as there are several provisions governing the consultation between the OJK and the House of Representatives (DPR) which can affect the independence of the former. The challenges faced by OJK in maintaining the stability of the national financial sector should be supported by providing independent authority, especially in aspects of regulation and supervision. This is due to the fact that the regulatory and supervisory aspects are the primary factors that reflect the integrity of stakeholders in OJK. The existence of a budget supervision for OJK and its consultation body with the DPR provides challenges for the OJK in the planning, implementation and evaluation process of the work programs being developed. The potential intervention from DPR towards the authority of OJK should be based on the importance of understanding the regulatory, supervisory, institutional and budgetary independence mechanisms so that they serve a positive impact on the development of the institutional role of OJK in managing the financial services sector.Keywords: Financial Services Authority, House of Representatives, Independence. AbstrakPenelitian ini bertujuan untuk menganalisa Independensi OJK setelah di undangkannya UU No. 4 Tahun 2023 tentang Pengembangan dan Penguatan Sektor Jasa Keuangan. Penelitian ini menjawab permasalahan bagaimana independensi OJK pasca diundangkan UU No. 4 Tahun 2023 tentang Pengembangan dan Penguatan Sektor Jasa Keuangan dan apa tantangan yang dihadapi oleh OJK dalam membangun hubungan antar kelembangan sektor jasa keuangan pasca diundangkan UU Nomor 4 Tahun 2023 tentang Pengembangan dan Penguatan Sektor Jasa Keuangan. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan undang-undang dan konseptual. Penelitian ini menyimpulkan bahwa dengan diterbitkannya UU No. 4 Tahun 2023 tentang Pengembangan dan Penguatan Sektor Jasa Keuangan memberikan tantangan dalam menjaga independensi OJK dalam menjalankan kewenangannya karena terdapat beberapa ketentuan terkait konsultasi antara OJK dan DPR yang dapat memengaruhi independensi OJK. Tantangan yang dihadapi oleh OJK dalam menjaga stabilitas sektor keuangan nasional hendaknya didukung dengan memberikan kewenangan yang bersifat independen khususnya pada aspek regulasi dan supervisi. Hal ini dikarenakan aspek regulasi dan supervisi merupakan faktor utama yang merefleksikan integritas OJK pada stakeholders. Keberadaan badan supervisi dan konsultasi anggaran OJK dengan DPR memberikan tantangan bagi OJK dalam proses perencanaan, implementasi, serta evaluasi atas program kerja yang dikembangkan. Potensi intervensi DPR atas kewenangan OJK hendaknya didasarkan atas pentingnya memahami mekanisme independensi yang bersifat regulasi, supervisi, kelembagaan, dan anggaran sehingga memberikan dampak positif bagi perkembangan peran kelembagaan OJK dalam mengelola sektor jasa keuangan.Kata Kunci: Dewan Perwakilan Rakyat, Independensi, Otoritas Jasa Keuangan.